Cold Shock Proteins Promote Nisin Tolerance in Listeria monocytogenes Through Modulation of Cell Envelope Modification Responses - Muchaamba, Francis; Wambui, Joseph; Stephan, Roger; Tasara, Taurai (Frontiers in Microbiology, 2021)
Listeria monocytogenes continues to be a food safety challenge owing to its stress tolerance and virulence traits. Several listeriosis outbreaks have been linked to consumption of contaminated ready-to-eat (RTE) food products. Numerous interventions including nisin application are presently employed to mitigate against L. monocytogenes risk in food products. In response, L. monocytogenes deploys several defense mechanisms reducing nisin efficacy that are not yet fully understood. Cold shock proteins (Csps) are small highly conserved nucleic acid binding proteins involved in several bacterial gene regulatory processes to mediate various stress responses in bacteria. L. monocytogenes possesses three csp gene paralogs; cspA, cspB and cspD. Using a panel of single, double, and triple csp gene deletion mutants the role of Csps in L. monocytogenes nisin tolerance was examined demonstrating their importance in nisin stress responses of this bacterium. Without csp genes, a L. monocytogenes ∆cspABD mutant displayed severely compromised growth under nisin stress. Characterizing single (∆cspA, ∆cspB, and ∆cspD) and double (∆cspBD, ∆cspAD, and ∆cspAB) csp gene deletion mutants revealed a hierarchy (cspD>cspB>cspA) of importance in csp gene contribution towards the L. monocytogenes nisin tolerance phenotype. Individual eliminations of either cspA or cspB improved the nisin stress tolerance phenotype suggesting that their expression has a curbing effect on expression of nisin resistance functions through CspD. Gene expression analysis revealed that Csp deficiency altered expression of DltA, MprF, and Penicillin binding protein encoding genes. Furthermore, the ∆cspABD mutation induced an overall more electronegative cell surface enhancing sensitivity to nisin and other cationic antimicrobials as well as the quaternary ammonium compound disinfectant benzalkonium chloride. These observations demonstrate that Csps molecular functions regulate systems important for enabling constitution and maintenance of an optimal composed cell envelope that protects against cell envelope targeting stressors including nisin. Overall, our data show an important contribution of Csps for L. monocytogenes stress protection in food environments where antimicrobial peptides are used. Such knowledge can be harnessed in development of better L. monocytogenes control strategies. Furthermore, the potential that Csps have in inducing cross-protection must be considered when combining hurdle techniques or using them in series.